ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL â€œSAN PEK ENG TAYâ€ SUATU TINJAUAN PSIKOLOGI SASTRA - THAM, JULIANA ELISA; IMBANG, DJEINNIE; LUMEMPOUW, FEMMY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis study aims to identify and describe (1) the main character in Oey Kim Tiang's San Pek Eng Tay novel and (2) moral message which author would like to highlight through the San Pek Eng Tay. descriptive analytic method is used in this research. In this method, the researcher divides the research in to two stages, analyzing the psychological approach of the main character Eng Tay based on thr character theory according to Hippocrates and Galenus. Secondly, analyzing the moral message based on the attitude, behavior, and moral order according to Sugiarti (2018) of this novel. Descriptive method is employed in this research which is to describe everything as it is (Keraf, 1981 in Breyvi). In this research, the researcher identifies and analyzes the main character in the adaptation novel of San Pek Eng Tay. The data collection is done through involvingÂ all dialogues of the main character (Population) to determine the character of every main character roles which are considered in accordance with the study and theory used with the stages of identify, classify, and then followed by description based on the aim of this study found that through the literary psychology approach illustrated the character of the main character which is strong, full of struggle, namely fighting for their right and obligation. In other words, the main character is persistent. The moral message in San Pek Eng tay is that in walking through life, which is fighting for something good, it must continue to be fought with persistence. This is showed through the role of Ciok Eng tay with her resilience in fighting thr rights and obligation as a woman; hence the Indonesian proverb of â€œEffort will not betray resultsâ€ is answered thus, do not give up easily.Â Keywords: Main Character Character, Moral Message and Novel